2022
DOI: 10.3390/insects13030247
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Populations of the Anopheles gambiae Complex in Southwest Burkina Faso Evolve Multiple Diverse Resistance Mechanisms in Response to Intense Selection Pressure with Pyrethroids

Abstract: Pyrethroid resistance in the Anopheles vectors of malaria is driving an urgent search for new insecticides that can be used in proven vector control tools such as insecticide treated nets (ITNs). Screening for potential new insecticides requires access to stable colonies of the predominant vector species that contain the major pyrethroid resistance mechanisms circulating in wild populations. Southwest Burkina Faso is an apparent hotspot for the emergence of pyrethroid resistance in species of the Anopheles gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…coluzzii strains Three insecticide resistant An. coluzzii strains from Burkina Faso: VK7 2014, Banfora M and Tiefora (origin and colonization date shown in Supporting Information, Table S1), that show mortality less than 13% after 1 h exposure to standard WHO bioassays with the pyrethroids deltamethrin, permethrin and alpha cypermethrin and to the organochloride DDT (previously described in 19,20 ), were tested for the presence of VGSC mutations L995F, I1527T, P1874S/L and V402L (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…coluzzii strains Three insecticide resistant An. coluzzii strains from Burkina Faso: VK7 2014, Banfora M and Tiefora (origin and colonization date shown in Supporting Information, Table S1), that show mortality less than 13% after 1 h exposure to standard WHO bioassays with the pyrethroids deltamethrin, permethrin and alpha cypermethrin and to the organochloride DDT (previously described in 19,20 ), were tested for the presence of VGSC mutations L995F, I1527T, P1874S/L and V402L (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Genes implicated in the cuticular hydrocarbon (CHC) synthetic pathway are upregulated in Banfora M, Bakaridjan and Gaoua-ara strains, though downregulated in Tiefora and VK7 2014, and it seems that cuticular resistance may be particularly signi cant in Gaoua-ara. 20 Using a commercially available dust product, sold for the control of household pest insects, this study provides a dramatic demonstration of the potential to overcome pyrethroid resistance mechanisms by manipulating the properties of crystalline insecticides. There is a very limited number of insecticides available for use in public health, and the discovery and development of new compounds is slow and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethroidresistance is widely spread across all regions in Benin [30][31][32][33][34] . In fact, this situation is associated with the recent massive deployment of LLINs across endemic countries for control of malaria, which led to selection pressure on mosquito vectors [35,36] . In addition, the use of pyrethoids in agriculture in the study area as reported in many other rural settings in Benin [37,38] might have contributed to the high frequency of kdr mutation recorded.…”
Section: Discussionmentioning
confidence: 99%